2008
DOI: 10.1111/j.1398-9995.2007.01624.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of control of severe asthma is associated with co‐existence of moderate‐to‐severe rhinitis

Abstract: In a population with severe asthma, moderate/severe rhinitis is a strong predictor for greater severity of asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
1
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(80 citation statements)
references
References 28 publications
3
69
1
7
Order By: Relevance
“…(19) A recent prospective cohort study carried out in Salvador revealed greater severity of asthma in patients who had concomitant rhinitis. (20) In adults, severe asthma was a risk factor for ER visits due to asthma exacerbations, which is in accordance with previous observations indicating the association between inflammation and asthma severity. (19) Severe asthma is responsible for a higher number of hospitalizations and ER visits and, therefore, represents a high burden to the health care system.…”
Section: Discussionsupporting
confidence: 80%
“…(19) A recent prospective cohort study carried out in Salvador revealed greater severity of asthma in patients who had concomitant rhinitis. (20) In adults, severe asthma was a risk factor for ER visits due to asthma exacerbations, which is in accordance with previous observations indicating the association between inflammation and asthma severity. (19) Severe asthma is responsible for a higher number of hospitalizations and ER visits and, therefore, represents a high burden to the health care system.…”
Section: Discussionsupporting
confidence: 80%
“…The definition of multi-symptom asthma used in the current study is not sufficient to encompass all aspects of severe asthma, as previously described in the literature, but many similarities are present. First, ''severe asthma'' has primarily been investigated in clinical cohorts [2,4,[18][19][20], but rarely in random population cohorts [9]. However, the current study reflects a population with signs of more severe disease and has a sex distribution, with females being more frequently affected, that is similar to what was reported in the populationbased European Community Respiratory Health Survey (ECHRS), where prognostic factors for asthma severity according to GINA were investigated [9], and to the patientbased European Network for Understanding Mechanisms of Severe Asthma (EMFUMOSA) [2,21].…”
Section: Discussionmentioning
confidence: 99%
“…Co-morbidity of other upper airway diseases including chronic rhinosinusitis with or without nasal polyps have also been linked to asthma severity. Many studies have reported that the severity of nasal and sinus disease parallel that of the lower airway disease (Pearlman et al, 2009;Ponte et al, 2008). On the other hand, the presence of nasal polyposis accompanying chronic rhinosinusitis and the duration of diseases were found to be correlated with extensive paranasal sinus computed tomography findings, and were related to the severity of asthma in adults (Dursun et al, 2006).…”
Section: Clinical Aspectsmentioning
confidence: 90%
“…Those patients whose allergic rhinitis was mild or well controlled, had better asthma control. Therefore, this data suggest that effective treatment of one disease may improve the other (Henriksen & Wenzel, 1984;Ponte et al, 2008). The study by Crystal-Peters et al was a retrospective cohort design to evaluate the treatment effects of AR on asthma-related health care resource utilization.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%